2011
DOI: 10.1161/circresaha.110.235689
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 Prevents Cardiac Rupture and Dysfunction After Myocardial Infarction

Abstract: These results suggest that Syn4 plays an important role in the inflammatory response and granulation tissue formation, thereby preventing cardiac rupture and dysfunction after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 52 publications
(62 reference statements)
7
94
2
1
Order By: Relevance
“…This conclusion is supported by a recent clinical study demonstrating that low levels of the circulating receptor for advanced glycation end products ectodomain were associated with increased risk of HF 72. In contrast, overexpression of a syndecan‐4 ectodomain preceding MI induction augmented the incidence of cardiac rupture and impaired heart function, apparently attributed to impaired granulation tissue formation and reduced myofibroblast numbers 73. However, a synergistic effect of a soluble receptor ectodomain moiety and its ligand triggering cell death has not been described yet.…”
Section: Discussionmentioning
confidence: 68%
“…This conclusion is supported by a recent clinical study demonstrating that low levels of the circulating receptor for advanced glycation end products ectodomain were associated with increased risk of HF 72. In contrast, overexpression of a syndecan‐4 ectodomain preceding MI induction augmented the incidence of cardiac rupture and impaired heart function, apparently attributed to impaired granulation tissue formation and reduced myofibroblast numbers 73. However, a synergistic effect of a soluble receptor ectodomain moiety and its ligand triggering cell death has not been described yet.…”
Section: Discussionmentioning
confidence: 68%
“…Findings by Matsui et al also support a role for syndecan-4 in this process, since they found impaired myofibroblast differentiation in the infarcted region after coronary ligation in syndecan-4 -/-mice [33].…”
Section: Discussionmentioning
confidence: 76%
“…One possibility is the engagement of MRTF-A which translocates to the nucleus in response to mechanical stress in a Rho kinase-dependent manner [39,40] and has also been shown to cause myofibroblast marker gene expression in cardiac fibroblasts [41]. Interestingly, RhoA activity (which in turn activates Rho kinase) is reduced in cardiac fibroblasts from syndecan-4 -/-mice [33]. Furthermore, NFATc4 over-expression resulted in increased MRTF-A mRNA, which may in turn promote myofibroblast differentiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…108,109 Because of its anchoring to the cytoskeleton 110,111 and the ECM 112 it is believed to function as a mechanosensor. In the heart, syndecan-4 has been shown to be upregulated in disease 96,[113][114][115] and to mediate mechanical stress-induced remodeling. [114][115][116] …”
Section: 105mentioning
confidence: 99%
“…Due to the regulation of syndecan-4 during cardiac remodeling and inflammation 96,[113][114][115] , it is likely that syndecan-4 as a biomarker can provide information about the pathogenesis of heart failure, especially with regard to inflammation in the myocardium.…”
Section: 211mentioning
confidence: 99%